Exploratory longitudinal studies on cerebral small vessel disease (CSVD) in apparently asymptomatic individuals with neuropsychological, neuroimaging and microparticles profiling - Nassir, Che Mohd Nasril Che Mohd (2018)
The prevalence of cerebral small vessel disease (CSVD) for asymptomatic (‘silent’) manifestation is typically obtained from incidental findings of white matter hyperintensities (WMHs) on magnetic resonance imaging (MRI). This study aimed to explore novel surrogate markers for the assessment of white matter integrity in CSVD among apparently asymptomatic individuals with neuropsychological, neuroimaging and microparticles (MPs) profiling. The recruited subjects with low to moderate cardiovascular risk prediction score as defined by QRISK2 underwent MRI brain scan, followed by neuropsychological indices of Weschler Adults Intelligence Scale (WAIS-IV) that measured their perceptual reasoning (PRI), working memory (WMI) and processing speed (PSI). Prior to flow cytometry MPs subpopulations enumerations, 18 ml of fasting blood was collected. Similar procedures were carried out at baseline (T0) and at 12 months follow-up (T12). At baseline, 48 asymptomatic individuals were recruited (mean age: 38.81±10.9); 24 were young adults, YA (mean age 29.7±4.33) and 24 mature adults, MA (mean age: 47.92±7.01). Fifteen (29.4%) had WMHs (WMH+) detected, of who five were YA, and 10 were MA. However, after one-year, 40 (mean age: 39.35±11.31) were able to participate; eight (20%) subjects were lost to follow up fourteen (35%) subjects were WMH+ and 26 (65%) were WMHAge influenced the presence of WMHs and WMH+ subject as having higher risk of CSVD. WMH+ subjects showed higher mean percentage of QRISK2 and MPs especially platelet derived MPs (CD41a and CD62P). In term of white matter integrity, QRISK2 score increased with reduced integrity (measured by fractional anisotropy, FA) of white matter tracts of superior corona radiata (SCR) and superior longitudinal fasciculus (SLF). White matter integrity was also reduced with advancing age. The PRI and WMI performance varied between subjects, but PSI consistently lower in WMH+ subjects. There were no significant temporal changes on cognitive and memories performances from both groups. FA of all tracts consistently and positively correlated with neuropsychological profiles. The integrity of white matter tracts such as left SLF and left anterior corona radiata were correlated with red blood cell MPs (CD235a) (r= -0.313, p=0.030) and CD62P (r=0.289, p= 0.047), respectively. Although with a relatively small sample size and one-year follow-up period, this study had established the correlations between cardio-cerebrovascular risk prediction by QRISK, neuropsychological indices performance, WMHs/white matter integrity from diffusion MRI and MPs profiling as potential surrogate markers for CSVD in apparently asymptomatic individuals.